Prevalence, incidence, primary care burden and medical treatment of angina in Scotland: age, sex and socioeconomic disparities: a population-based study. Issue 8 (6th January 2006) - Murphy, N F; Simpson, C R; MacIntyre, K; McAlister, F A; Chalmers, J; McMurray, J J V
Abstract : Objective: To examine the epidemiology, primary care burden and treatment of angina in Scotland. Design: Cross-sectional data from primary care practices participating in the Scottish continuous morbidity recording scheme between 1 April 2001 and 31 March 2002. Setting: 55 primary care practices (362 155 patients). Participants: 9508 patients with angina. Results: The prevalence of angina in Scotland was 28/1000 in men and 25/1000 in women (p < 0.05) and increased with age. The prevalence of angina also increased with increasing socioeconomic deprivation from 18/1000 in the least deprived category to 31/1000 in the most deprived group (p < 0.001 for trend). The incidence of angina was higher in men (1.8/1000) than in women (1.4/1000) (p  =  0.004) and increased with increasing age and socioeconomic deprivation. Socioeconomically deprived patients (0.48 contacts/patient among the most deprived) were less likely than affluent patients (0.58 contacts/patient among the least deprived) to see their general practitioner on an ongoing basis p  =  0.006 for trend). Among men, 52% were prescribed β blockers, 44% calcium channel blockers, 72% aspirin, 54% statins and 36% angiotensin converting enzyme inhibitors or angiotensin receptor blockers. The corresponding prescription rates for women were 46% (p < 0.001), 41% (p  =  0.02), 69% (p < 0.001), 45% (p < 0.001) and 30% (p < 0.001). Among patients < 75 years old 52% were prescribed a β blocker and 58% a statin. The corresponding figures for patients ⩾ 75 years were 42% (p < 0.001) and 31% (p < 0.001). Conclusions: Angina is a common condition, more so in men than in women. Socioeconomically deprived patients are more likely to have angina but are less likely to consult their general practitioner. Guideline-recommended treatments for angina are underused in women and older patients. These suboptimal practice patterns, which are worst in older women, are of particular concern, as in Scotland more women (and particularly older women) than men have angina.